2022
DOI: 10.3389/fsurg.2022.999406
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the efficacy and safety of bone cement in the treatment of endplate fractures

Abstract: BackgroundEndplate fractures is an important factor affecting the curative effect of percutaneous kyphoplasty for spinal fracture. The purpose of this study is to investigate the effect of sealing endplate fracture with bone cement on minimally invasive treatment of spinal fracture.MethodsA total of 98 patients with osteoporotic vertebral fractures combined with endplate fractures treated with bone cement surgery in our hospital were retrospectively analyzed. They were grouped according to whether bone cement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Sun et al (13) reported that cement distribution proximal to the adjacent vertebral body (distributed at the disc level or endplate level) could increase the risk of post-vertebroplasty fractures in adjacent vertebral bodies. Similarly, Zhao et al (37) found that the diffusion of bone cement into cracks in the injured endplate may increase the incidence of adjacent vertebral fractures. These results further explain the differences in the numbers of DDC cases induced by different cement distribution patterns.…”
Section: Discussionmentioning
confidence: 92%
“…Sun et al (13) reported that cement distribution proximal to the adjacent vertebral body (distributed at the disc level or endplate level) could increase the risk of post-vertebroplasty fractures in adjacent vertebral bodies. Similarly, Zhao et al (37) found that the diffusion of bone cement into cracks in the injured endplate may increase the incidence of adjacent vertebral fractures. These results further explain the differences in the numbers of DDC cases induced by different cement distribution patterns.…”
Section: Discussionmentioning
confidence: 92%
“…When the endplate fractures, the pressure it bears is uneven, leading to accelerated degeneration of the intervertebral disc ( 42 ). Studies have found that patients with endplate fractures who undergo cement surgery have an increased risk of cement leakage and may even experience fractures in other vertebral bodies ( 43 ). Based on these two points, when the bone cement seeps into the intervertebral disc through the fracture line of the endplate, it undergoes degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that endplate destruction leads to stress concentration, thereby compromising the biomechanical stability of the spinal column. Moreover, the loss of endplate integrity may lead to bone cement leakage, both of which contribute to the increased incidence of NVCF [ 45 , 46 ]. However, further investigations are required to determine whether endplate repair can mitigate NVCF occurrence in patients with osteoporosis.…”
Section: Discussionmentioning
confidence: 99%